Integrating Leadership Education into Urology Residency Training. Issue 1 (January 2018) - Ziemba, Justin B.; Ziemba, Thomas M.; Pietzak, Eugene J.; Guzzo, Thomas J.; Canning, Douglas A.; Wein, Alan J.
Abstract : Introduction: : Leadership is an integral component of medical practice. Nevertheless, during residency minimal attention is paid to developing this important domain. Therefore, we report on our experience with a formal leadership curriculum for senior urology residents. Methods: : In consultation with a leadership expert a curriculum was developed with readings and discussion questions focusing on understanding and applying leadership theory. A symposium was then organized to discuss leadership theory as applied to clinical practice and debate how to be a successful leader in urology. Results: : Our first cohort of residents completed the curriculum in 2015. Due to its success it was repeated for a second cohort of residents in 2016. A formal assessment of the curriculum showed that 91% (10 of 11) and 73% (8 of 11) of residents strongly or somewhat agreed that they will adopt new leadership strategies and are more confident as leaders, respectively. Conclusions: : We developed and successfully implemented a leadership curriculum for urology residents. The curriculum goals were met with participants reporting that they acquired new leadership strategies and had increased confidence as a leader. We now expand on these initial efforts by proposing the core leadership dimensions for residents of managing the self, managing the clinical experience and managing the clinical team. In each dimension there are specific competencies that can be mapped to measure resident performance over time. It is our hope that this conceptual framework will help guide future local and national surgical leadership training.